Review and assessment of the different categories of demand response potentials - Dranka, Geremi Gilson (2019)
Demand Response (DR) is a well-known concept which has been recognized as an increasingly valuable tool to provide flexibility to the power system, to support the integration of Variable Renewable Energy (VRE) resources and to manage the grid more efficiently. In recent years, there have been a growing number of publications focusing on the estimation of different categories of DR potentials (e.g. theoretical, technical, economic, and achievable) using different methodologies and assumptions in each research study. The contribution of the present study is twofold. Firstly, a literature review is undertaken focusing specifically on the categorization of the scientific approaches used to estimate the different categories of DR potentials. To the best of authors' knowledge, a general procedure for the estimation of each DR potential category is still missing. Therefore, a novel user-friendly and step-by-step theoretical framework for the determination of the different categories of DR potentials is presented. Findings of this study reveal that literature has extensively focused on the estimation of the technical DR potential followed by the economic, theoretical and achievable potentials respectively. A lack of understanding of the different categories of DR potentials was also identified, which sometimes have been unduly used in the literature. The proposed framework is supported on a small sample of numerical approaches and equations which results in a structured approach to bringing consensus to the DR potential assessment. (C) 2019 Elsevier Ltd. All rights reserved.